Diversion of the paleo‐Yellow River channel in the Qingtongxia area of Ningxia, China: Evidence from terraces and fluvial landforms. (20th November 2019) - Chen, Hong; Bao, Guo‐dong; Shi, Wei; Hu, Jian‐min
Abstract : The Qingtongxia Grand Canyon (QGC) of the Yellow River is a region of intense tectonic deformation that is located in the southern Yinchuan Basin, at the junction of the western margin of the Ordos Plateau and the northeast arcuate structural belt of the Qinghai–Tibetan Plateau. The Yellow River makes a 90° turn as it traverses the Qingtongxia area, incising the hard Ordovician sandstones of Niushou Mountain, while leaving the relatively soft Quaternary sediments on the northern side of the channel undisturbed. Despite this apparent inconsistency with the expected pattern of river erosion, there has been no significant research to date on the formation of the QGC. Here, we utilize remote sensing, surficial geomorphology, and shallow coring to confirm the evolution of the Yellow River channel and formation of the QGC. Using Landsat Thermic Mapper and ASTER imagery, we identified a N–S‐oriented zone of high water‐content in the northern part of the QGC that is characterized at the surface by marsh and wetlands. Shallow cores reveal the zone is underlain by Yellow River gravel, while seismic profiling confirms anomalous seismic structures relative to the surrounding strata. Together, these data document a paleo‐Yellow River channel in the northern Qingtongxia area. We selected four representative profiles of the Yellow River terraces in the Qingtongxia and adjacent areas to acquire measurements on above water level and age. The uppermost terraces preserved at the entrance, central section, and exit of the QGC are labelled T6, T9, and T3, respectively. Our data indicate that the flow direction during the construction of T9 was different to that of the modern Yellow River and that canyon incision occurred during the development of T3, which we constrain to 65–85 ka. Ultimately, we (a) document a paleo‐Yellow River channel north of the QGC, which may have been affected by tectonic activity since the late Pleistocene and (b) show that the Yellow River has since been diverted towards the Yinchuan Basin via the QGC.